Teknik Terapi Radiasi 3DCRT Pada Kasus Kanker Serviks Dengan Studi Literatur - Derill Kyuya Ngongoloy; Anak Agung Aris Diartama; Kadek Yuda Astina (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2024)
Research with literature studies is still rarely carried out, therefore in this article we want to know about the External Radiation Radiotherapy Technique in Cervical Cancer Cases with 3D-CRT (3-Dimensional Conformal Radiation Therapy): This literature discusses the application of the 3D-CRT external radiation radiotherapy technique in treatment cervical cancer. 3D-CRT is a method that allows external radiation exposure from more than one side,possiblemore appropriate radiation dose according to the shape and location of the tumor. This study also lists other techniques such as Brachytherapy, IMRT, and 2D in the treatment of cervical cancer. Photon Dose Distribution Using 3D-CRT and IMRT Techniques in Cervical Cancer Therapy: This research discusses photon dose distribution in the Treatment Planning System (TPS) using 3DCRT and IMRT techniques for cervical cancer therapy. This provides insight into the comparison between the two techniques in delivering appropriate radiation doses to the tumor target. 6 MV Energy Linac Radiotherapy Against Cervical Cancer: This journal discusses the use of radiotherapy on a Linac aircraft with a 6 MV energy photon beam using the 3DCRT technique in the treatment of cervical cancer. This technique helps deliver the right dose of radiation according to the target area. The literature above provides information about external radiotherapy techniques, including 3D-CRT, in the treatment of cervical cancer. They help understand the role and application of this technique in cervical cancer treatment.